2009
DOI: 10.1093/pcp/pcp167
|View full text |Cite
|
Sign up to set email alerts
|

Knock-down of OsDCL2 in Rice Negatively Affects Maintenance of the Endogenous dsRNA Virus, Oryza sativa Endornavirus

Abstract: An endogenous double-stranded RNA (dsRNA), which has recently been recognized as the dsRNA virus Oryza sativa endornavirus (OsEV), is found in many strains of cultivated rice (Oryza sativa). Small RNAs derived from OsEV dsRNA were detected, indicating that the RNA silencing machinery recognizes OsEV dsRNA. The existence of OsEV in knock-down (KD) lines of five genes of RNA-dependent RNA polymerase (OsRDR1-OsRDR5) or two genes of Dicer-like protein (OsDCL2 or OsDCL3a) was examined to characterize the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This indicates that the generation of the 21-nt and 22-nt-long hairpin-derived siRNAs is independent of DCL1 and DCL3 activities. This observation combined with the previous findings in rice (Liu et al 2007;Urayama et al 2010) that DCL4 was responsible for the 21-nt siRNA generation and DCL2 for the 22-nt ones, led us to conclude that the long-hairpin-derived 21-nt, 22-nt, and 24-nt siRNAs were the products of DCL4-, DCL2-, and DCL3-mediated cleavages, respectively.…”
Section: Hairpin-structured Introns Generating Both Mirnas and Sirnassupporting
confidence: 76%
See 1 more Smart Citation
“…This indicates that the generation of the 21-nt and 22-nt-long hairpin-derived siRNAs is independent of DCL1 and DCL3 activities. This observation combined with the previous findings in rice (Liu et al 2007;Urayama et al 2010) that DCL4 was responsible for the 21-nt siRNA generation and DCL2 for the 22-nt ones, led us to conclude that the long-hairpin-derived 21-nt, 22-nt, and 24-nt siRNAs were the products of DCL4-, DCL2-, and DCL3-mediated cleavages, respectively.…”
Section: Hairpin-structured Introns Generating Both Mirnas and Sirnassupporting
confidence: 76%
“…In both Arabidopsis and rice, DCL3 is involved in the biogenesis of the 24-nt siRNAs and lmiRNAs (long microRNAs) (Xie et al 2004;Chellappan et al 2010;Wu et al 2010), whereas DCL4 is responsible for the production of 21-nt siRNAs from IR genes and the ta-siRNAs (Vazquez et al 2004;Gasciolli et al 2005;Xie et al 2005;Liu et al 2007). DCL2 plays a major role in processing siRNAs from endogenous dsRNA virus in rice (Urayama et al 2010); presumably a similar role is possessed by its homolog in Arabidopsis (Kapoor et al 2008), which was suggested to be engaged in producing 22-nt siRNAs for viral resistance (Xie et al 2004). Distinct kinds of siRNAs are incorporated into specific AGO-associated RISCs, guiding the complexes to the DNA or RNA targets based on sequence complementarity and triggering gene silencing transcriptionally or post-transcriptionally.…”
Section: Introductionmentioning
confidence: 99%
“…However, dcl2 and dcl3 mutants in Arabidopsis have no obvious developmental defects under normal growth conditions. In rice, knock‐down of OsDCL2 produced a dwarf plant with significantly lower spikelet fertility and negatively affected maintenance of an endogenous dsRNA virus by increasing the accumulation of virus siRNAs (Urayama et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous double-stranded RNA (dsRNA) nowadays known as dsRNA virus in rice Oryza sativa Endornavirus (osEV) which found in several cultivars of rice [93]. Small RNAs which were derived from osEV dsRNA were identified, demonstrating that RNA silencing distinguishes the osEV dsRNA.…”
Section: Role Of Rdrs Agos and DCL Enzymes As Silencing Suppressormentioning
confidence: 99%